Stress appraisals, coping, and coping effectiveness among international cross-country runners during training and competition - Nicholls, A. R.; Levy, A. R.; Grice, A.; Polman, R. C. J. (European Journal of Sport Science, 2009)
The aims of this study were to explore: (a) stressors (including intensity of the feelings that the appraisal of each stressor generated and control of the stressor) and coping strategies on training and competition days; (b) the relationship between stressor intensity and stressor control; (c) the relationship between stressor intensity and stressor control with coping effectiveness; and (d) the relationship between coping effectiveness and coping automaticity. Participants were 10 elite Caucasian cross-country athletes who maintained a stressor and coping diary for 6 weeks. Results revealed that the runners experienced diverse stressors and used different coping strategies on training and competition days. Stressors were significantly more intense on competition days. Additionally, there was a significant negative correlation between stressor intensity and stressor control, and a negative correlation between stressor intensity and coping effectiveness. These results support the notion that stressors and coping are situation-specific variables. Applied practitioners could thus devise situation-specific coping interventions to maximize coping effectiveness.